2012
DOI: 10.2174/187152512800388939
|View full text |Cite
|
Sign up to set email alerts
|

PF-04886847 (an Inhibitor of Plasma Kallikrein) Attenuates Inflammatory Mediators and Activation of Blood Coagulation in Rat Model of Lipopolysaccharide (LPS) - Induced Sepsis

Abstract: The plasma kallikrein-mediated proteolysis regulates both thrombosis and inflammation. Previous study has shown that PF-04886847 is a potent and competitive inhibitor of kallikrein, suggesting that it might be useful for the treatment of kallikrein-kinin mediated inflammatory and thrombotic disorders. In the rat model of lipopolysaccharide (LPS) -induced sepsis used in this study, pretreatment of rats with PF-04886847 (1 mg/kg) prior to LPS (10 mg/kg) prevented endotoxin-induced increase in granulocyte count i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Other PKal inhibitors have indeed been reported to more markedly impact the aPTT coagulation time. E.g., KALI-DY, an engineered molecule obtained from Kunitz domain phage libraries, prolonged the aPTT clotting time by more than 3.5-fold at 1 μM, and PF-04886847, a small molecule competitive inhibitor of PKal, increased the aPTT clotting time 2-fold at 14 μM . However, both KALI-DY and PF-04886847 inhibit Factor XIa at K i = 8.2 nM and 1 μM, respectively, , which should amplify their activity in the aPTT assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other PKal inhibitors have indeed been reported to more markedly impact the aPTT coagulation time. E.g., KALI-DY, an engineered molecule obtained from Kunitz domain phage libraries, prolonged the aPTT clotting time by more than 3.5-fold at 1 μM, and PF-04886847, a small molecule competitive inhibitor of PKal, increased the aPTT clotting time 2-fold at 14 μM . However, both KALI-DY and PF-04886847 inhibit Factor XIa at K i = 8.2 nM and 1 μM, respectively, , which should amplify their activity in the aPTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…E.g., KALI-DY, an engineered molecule obtained from Kunitz domain phage libraries, prolonged the aPTT clotting time by more than 3.5-fold at 1 μM, 33 and PF-04886847, a small molecule competitive inhibitor of PKal, increased the aPTT clotting time 2-fold at 14 μM. 52 However, both KALI-DY and PF-04886847 inhibit Factor XIa at K i = 8.2 nM and 1 μM, respectively, 33,53 which should amplify their activity in the aPTT assay. It is therefore conceivable that the more limited effect of 1b and 2d on the aPTT clotting time is in fact due to their highly specific selectivity profile against other serine proteases from the clotting cascade.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Comparison of the complexes of PK with 42a (b) and benzamidine (d; PDB code 2ANY ) shows that overall the substrate-binding sites are similar with comparatively little induced fit in the complex with 42a . Peptidomimetic (kallistop, 43 ; MDCO-2010, 45 ) and nonpeptidic (PF-04886847, 44 ) PK inhibitors are also known, and a likely PK binding mode for 43 (based on docking to the 4ZJ6 receptor) is shown in panel e. This compound makes many similar contacts with PK as the peptide 42a and additionally forms polar interactions between the ligand benzoic acid group and the K147 residue. (f) The pharmacophoric similarity between the small-molecule PK inhibitors is evident from flexible alignment of 43 (magenta) and 44 (cyan) with the modeled bioactive conformation of 45 (green).…”
Section: Drug Discovery Overviewmentioning
confidence: 99%
“…Using a balloon-induced femoral artery injury model in hypercholesterolemic rabbits, we recently demonstrated that intravenous administration of a potent, small molecule plasma kallikrein inhibitor significantly reduced thrombus mass with minimal effect on bleeding time. 37,38 Similarly, other plasma kallikrein inhibitors have also shown to have antithrombotic properties in vitro or in animal models of venous and arterial thrombosis ( Table 1). [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] These studies provide strong evidence that although components of the plasma KKS are dispensable for normal hemostasis, they play a central role in pathological thrombus formation.…”
Section: Plasma Kallikrein: Synthesis Structure and Functionsmentioning
confidence: 99%